A Multi-Stakeholder System-Based Methodology to Evaluate the Needs of Innovation Ecosystems - Palominos-Belmar, P; Alfaro-Marchant, M (Springer Science and Business Media Deutschland GmbH, 2021)
The current nature of innovation projects, which integrate a growing number of stakeholders, is increasing the complexity and scope of the product development process. The understanding of the complex and synergistic dynamics between the entire set of stakeholders requires well-adapted approaches to deal with this complexity since the early stages of a project. The present paper proposes a new methodology, based on the Kano model and needs trade-off methodology for a multi-stakeholders’ ecosystem during early design stages, enabling to identify and anticipate the needs of an ecosystem of stakeholders. The resulting aggregated Kano matrix enables a holistic vision of the aggregated stakeholders’ needs, and then identify emerging needs of the entire ecosystem. The proposed methodology is illustrated through a case study concerning an innovative project of self-directed learning tool apps for smartphones. © 2021, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.